Regulation and Ethics of Using Artificial Intelligence (AI) in Education - Dharliana Hardjowikarto; Handiriono, Raden; Kamil, Insan; Reza Pramadia (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
The development of digital technology today has brought significant changes in various sectors of life, including in the world of education. One of the technological innovations that is currently developing rapidly is the use of Artificial Intelligence. The use of Artificial Intelligence in education offers many potentials, such as personalized learning, automatic assessment, and increased administrative efficiency. However, behind these benefits, the use of Artificial Intelligence in education also faces problems that need to be addressed to ensure that its implementation is fair and transparent. This article aims to examine the legal regulations and ethics in the use of Artificial Intelligence in education. This study uses a normative legal approach method, namely focusing on the analysis of existing laws and regulations, as well as relevant legal theories. The results of the study show that although there have been several regulations covering the use of technology and personal data, specific and binding regulations regarding the use of Artificial Intelligence in education still do not exist. This creates legal uncertainty if someone experiences a loss in its use. Ethics in the use of AI in education must meet the principles of governance and management, transparency and accountability, sustainability and proportionality, privacy, security and safety, inclusiveness, and human-centered AIED. Some of the obstacles faced include technological gaps, supervision of the use of Artificial Intelligence, misuse of technology, and unprepared human resources. Therefore, it is necessary to develop specific regulations to regulate the use of Artificial Intelligence in education in order to maximize its benefits while protecting the legal rights of individuals, especially students, in the learning process.